The essence, types, and factors of the formation of competitive advantages of the enterprinse - Yemchuk, Tetiana (Higher school of social and economic Przeworsk: WSSG, 2019)
The competitive advantage of the company is the result of more effective than the competitor‘s process management of the formation and development of the qualitative and quantitative product properties that are important to the buyer.
Keywords: competitive advantage; marketing